Space and place: the perspective of experience - Tuan, Yi-Fu (Minneapolis University of Minnesota Press, 1977)
A study of the ways in which people feel and think about space, how they form attachments to home, neighborhood, and nation, and how feelings about space and place are affected by the sense of time.Since it is the breadth and universality of his argument that concerns Yi-Fu Tuan, experience is defined as all the modes by which a person knows and constructs reality, and examples are taken with equal ease from non-literate cultures, from ancient and modern oriental and western civilizations, from novels, poetry, anthropology, psychology, and theology. The result is a remarkable synthesis, which reflects well the subtleties of experience and yet avoids the pitfalls of arbitrary classification and facile generalization. For these reasons, and for its general tone and erudition and humanism, this book will surely be one that will endure when the current flurry of academic interest in environmental experience abates. Canadian Geographer